1995
DOI: 10.1093/ije/24.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Methods for Estimating Environmental Tobacco Smoke Exposure among Children Aged between 12 and 36 Months

Abstract: Nicotine measurement in hair is a practical and valid method for estimating average ETS exposure in children. An underreporting of ETS exposure was indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 0 publications
4
57
0
1
Order By: Relevance
“…Several studies indicate that hair nicotine concentration is a useful biomarker of longer term smoke exposure (Al-Delaimy et al, 2002;Eliopoulos et al, 1996;Nafstad et al, 1995;Pichini et al, 1997b). With a rate of hair growth of about 1.1 cm/month (Uematsu, 1993), a small amount of hair (2-3 cm) from the scalp can potentially represent exposure to SHS over 2-3 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicate that hair nicotine concentration is a useful biomarker of longer term smoke exposure (Al-Delaimy et al, 2002;Eliopoulos et al, 1996;Nafstad et al, 1995;Pichini et al, 1997b). With a rate of hair growth of about 1.1 cm/month (Uematsu, 1993), a small amount of hair (2-3 cm) from the scalp can potentially represent exposure to SHS over 2-3 months.…”
Section: Introductionmentioning
confidence: 99%
“…With a rate of hair growth of about 1.1 cm/month (Uematsu, 1993), a small amount of hair (2-3 cm) from the scalp can potentially represent exposure to SHS over 2-3 months. In addition, hair nicotine has shown better ability to discriminate exposure status when compared with urinary cotinine (Al-Delaimy et al, 2002;Nafstad et al, 1995). Al-delaimy et al reported that hair nicotine concentrations in a sample of children were more strongly associated with categories of smoking within a household (no smokers, smoking only outside the house, and smoking inside the house) than urinary cotinine concentrations (Al-Delaimy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hair nicotine has been used as a biomarker for assessing chronic exposure to ETS and active smoke, as it can cover wide time-windows (Nafstad et al 1995;Jaakkola and Jaakkola, 1997;Jaakkola et al, 2001;Segura et al, 2000). Determination of nicotine in the hair of pregnant women proved useful to obtain information on exposure in the whole gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Cotinine (a metabolite of nicotine ) in body fluids has been used in many studies for the assessment of ETS (Strachan et al, 1989;Benowitz and Jacob, 1993;Crawford et al, 1994;Haddow et al, 1994;Wang et al, 1997 ) , but its short half -life and the metabolic variability in clearance rates among individuals are some of the disadvantages (Coultas et al, 1990;Idle, 1990;Nelson, 1994 ). Levels of nicotine in hair may be a good alternative indicator for assessment of exposure ( Nafstad et al, 1995;Dimich-Ward et al, 1997;Pichini et al, 1997 ) , with the distinct advantage of reflecting long -term exposure. Each centimeter of hair represents more than 1 month of exposure because hair has a uniform growth rate of 1 0.3 cm /month (Uematsu et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%